Description of Women's Knowledge, Attitudes and Behavior Regarding the Use of Injectable Hormonal Contraception at the Midwife Ratna Clinic in Central Kalimantan - Elena, Irene Maria; Setiawan, Adrian; Darmasusila, Ida Bagus; Lestari, Diah Ayu (Jurnal MedScientiae, 2023)
Family planning is the effort to regulate the birth of children, the distance children and the ideal ageof childbirth, regulate pregnancy, through promotion, protection and assistance according toreproductive rights to realize quality families and improve welfare, infant and child health andreproductive health. In relation to the above conditions researchers wanted to know the level ofknowledge, attitude and behavior of women 20-39 years of use of injecting hormonal typecontraception. This research uses descriptive research with cross sectional method, the samplingtechnique used in this research is convenience sampling. The sample in this study amounted to 106respondents using inject type contraception. This research was done at ranta midwife clinic inkalteng. In the analysis and interpretation of data in use univariate analysis with descriptive method.Based on the results of the study of 106 samples, women using injectable contraceptives had less than82 people (74.4%), women who were negative about contraception 1 person (0.9%), women who hadless behavior about 15 injectable contraceptives (14.2%).